1966
DOI: 10.1128/jb.91.2.622-627.1966
|View full text |Cite
|
Sign up to set email alerts
|

Growth Responses ofNeurospora crassato Increased Partial Pressures of the Noble Gases and Nitrogen

Abstract: BUCHHEIT, R. G. (Union Carbide Corp., Tonawanda, N.Y.), H. R. SCHREINER, AND G. F. DOEBBLER. Growth responses of Neurospora crassa to increased partial pressures of the noble gases and nitrogen. J. Bacteriol. 91:622-627. 1966.-Growth rate of the fungus Neurospora crassa depends in part on the nature of metabolically "inert gas" present in its environment. At high partial pressures, the noble gas elements (helium, neon, argon, krypton, and xenon) inhibit growth in the order: Xe > Kr > Ar >> Ne >> He. Nitrogen (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1967
1967
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 22 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…On one hand, oxygen has been used during hypothermic preservation in experimental and clinical models of kidney transplantation but the protective effects against organ injury are still in debate [ 9 ]. On the other hand, noble gases, e.g., argon and xenon, have been used to preserve perishable foods by limiting oxidation [ 10 ] prior to their development for graft preservation [ 6 , 11 ]. Following this latter approach and using a rat model of kidney transplantation with a short cold-ischemia time (6 h), we reported that the use of the preservation solution Celsior saturated with pure argon (Argon-Celsior) improves graft functional recovery and limits IRI compared with the use of Celsior saturated with atmospheric air (Air-Celsior) [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…On one hand, oxygen has been used during hypothermic preservation in experimental and clinical models of kidney transplantation but the protective effects against organ injury are still in debate [ 9 ]. On the other hand, noble gases, e.g., argon and xenon, have been used to preserve perishable foods by limiting oxidation [ 10 ] prior to their development for graft preservation [ 6 , 11 ]. Following this latter approach and using a rat model of kidney transplantation with a short cold-ischemia time (6 h), we reported that the use of the preservation solution Celsior saturated with pure argon (Argon-Celsior) improves graft functional recovery and limits IRI compared with the use of Celsior saturated with atmospheric air (Air-Celsior) [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…High-pressure inert gases such as NZ, N?O, He, Ne, Ar, Kr and Xe have been studied to determine their effects on biological systems. Studies of this type have included the growth rate of the mold Nmrospora cra.s~a (Schreiner et al, 1962;Schreiner et al, 1963;and Buchheit et al, 1966), the growth of protozoans (Sears et al, 1961), the oxygen dependent radio sensitivity of plants (Ebert et al,19.58), the growth rate of mammalian epithelial cells (Bruemmer et al, 1967) and the activity of tyrosinase (Schreiner, 1965).…”
Section: Introductionmentioning
confidence: 99%
“…This inhibitory series for germination is similar to the series for narcotic potency and also to the series reported for growth inhibition. For example, Buchheit et al (3) presented a series for inhibition of growth of Neurospora crassa with Xe > Kr > Ar >> Ne >> He > N2; the partial pressures required for 50% inhibition of growth were, respectively: 0.08, 0.16, 0.38, 3.5, and ca. 30 MPa, with no value determined for N2 because it was not possible to achieve 50% growth inhibition with N2.…”
mentioning
confidence: 99%